ON THE COMPOSITION AND ORE POTENTIAL OF THE PRODUCTS OF THE OXIDIZING AND REDUCING STAGES IN THE WEATHERING OF CARBONATITES - Lapin A.V. (My University, 1990)
Study of regions of the lateritic weathering of carbonatites shows that among the supergene products developed in them, rocks differing essentially in composition can be distinguished, and that these correspond to fundamentally different conditions of supergene mineralization. Analysis of these differences indicates that many regions of lateritic weathering of carbonatites are characterized by a change in physicochemical environments and stages of weathering, which is manifested in a transition from the stage of lateritic weathering proper, with its typical oxidizing conditions and a dominant role of acid leaching, to a later reducing stage manifested in the superimposition of epigenetic gley-forming processes on the products of the oxidizing stage. Thus in the full profile of the lateritic weathering of carbonatites, from top to bottom, one can distinguish: a horizon of brown iron ores ('iron armor' or 'cuirass'), a thick sequence of unconsolidated ocherous products (the zone of leaching, or lithomarge), horizons of secondary redeposited francolite and quartz rocks (zone of cementation or secondary enrichment) and, finally, a zone of unevenly ferruginous or silicified distintegrated carbonatites.